Thyroid hormones and Corticosterone investigation under heat stress in native chicken - VARUN, A; OMPRAKASH, A V; KUMANAN, K; VAIRAMUTHU, S; KARTHIKEYAN, N (The Indian Journal of Animal Sciences, 2021)
The study was conducted to evaluate the effect of thermal conditioning on serum levels of Triiodothyronine (T3), thyroxine (T4) and corticosterone (CORT) in four different chicken strains namely Aseel, Naked Neck, Assel × Nandanam chicken-4 and Naked Neck × Nandanam Broiler-3. Chicks were divided into control (C; ambient temperature 28±1°C) and heat exposed groups (H; 39±1°C for 2 hours; 0-2 and 5-6 weeks of age). At 12th week, control group were divided into two groups, i.e. unexposed control (C) and exposed control (CE). Birds from H group (HE) and CE group were thermally challenged at 39±1°C for 4 hours daily on 12th week. On 42nd and 84th day, blood was withdrawn from each group, serum separated and processed for T3, T4 and CORT. The results indicated that the thermal conditioning had significantly decreased T3, T4 and increased CORT levels, irrespective of strains. At thermal challenge, a drastic drop in CORT level and improvement in thyroid hormone levels were noticed in the preconditioned birds. From present study, it was concluded that, the birds are able to withstand the heat stress effect which was indicated by drop in CORT level.